Sulfur mustard and respiratory diseases: Revisit with special reference to the "comments on 'Sulfur Mustard and Respiratory Diseases', Tang and Loke (2012) and a prepared Integrated Mechanism for Chronic Pulmonary Disease from Exposure to Sulfur Mustard'' by Saburi and Ghanei (2013) - Tang, F.R. (2014)
10.3109/10408444.2013.764843